Synthesis of Highly Functionalized Polycyclic Quinoxaline Derivatives Using Visible‐Light Photoredox Catalysis1. Issue 52 (27th October 2014) - He, Zhi; Bae, Minwoo; Wu, Jie; Jamison, Timothy F.
Abstract A mild and facile method for preparing highly functionalized pyrrolo[1, 2‐a]quinoxalines and other nitrogen‐rich heterocycles, each containing a quinoxaline core or an analogue thereof, has been developed. The novel method features a visible‐light‐induced decarboxylative radical coupling of ortho‐substituted arylisocyanides and radicals generated from phenyliodine(III) dicarboxylate reagents and exhibits excellent functional group compatibility. A wide range of quinoxaline heterocycles have been prepared. Finally, a telescoped preparation of these polycyclic compounds by integration of the in‐line isocyanide formation and photochemical cyclization has been established in a three‐step continuous‐flow system.